HUBUNGAN ANTARA LITERASI INFORMASI DENGAN HASIL BELAJAR ILMU UKUR TANAH SISWA: (Penggunaan Model The Big 6 Skills di SMKN 1 Jakarta) (LPPM Universitas Negeri Jakarta, 2019)
Abstract This study aims to determine the relationship between information literacy using the The Big 6 Skills model with student learning outcomes in the subjects of Land Measurement Science and Design Information Building expertise program. The type of research used in this study is associative quantitative research. The method used is a survey method with a correlational approach. The population in this study were students of class X of SMKN 1 Jakarta program. Using the Random Sampling technique the sample is filled with 80 respondents. The results showed that there was a positive and significant relationship between information literacy and learning outcomes as evidenced by: correlation coefficient of 0.615 which is included in the category of strong relationships, the significance value of the correlation coefficient t count = 7.854 and t table = 1.991 which indicates a significant relationship, and the relationship between information literacy and learning outcomes is obtained by the determination coefficient value of 0.38. Thus, it can be said that information literacy factors can affect learning outcomes by 38%, and the rest is influenced by other factors beyond the ability of information literacy. Keywords: Information Literacy, The Big 6 Skills, Learning Outcomes